Human Reproduction Contextual Case-Based Worksheet to Improve Students’ Interpersonal Communication and Collaboration Skills - Siti Alimah; Listyawati Utami (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2019)
Human reproduction in biology is included in the category of a topicthat cannot be sensed directly, but is close to the problems in the daily lives of students. It needs to be optimized in classroom learning, one of which is a worksheet based on human reproductive contextual case studies.This study aimed to find out the effect of human reproduction case-based worksheet on interpersonal communication and collaboration skills. The research method used was one hort case study design involving 68 students of Senior High School in Semarang. The data was analyzed by descriptive quantitative method. The results of the analysis showed that both of student's interpersonal communication and collaboration skills were invery high category.The teacher and student showed a positive response to the use of case-based worksheet in human reproduction learning activity. Based on the results of the study, it can be concluded that the human reproduction case-based worksheet improves interpersonal communication and collaboration skills in Senior High School student in Semarang.The teacher can use this contextual case-based worksheet as an alternative in human reproduction teaching and learning to explore, train and familiarize students' collaboration and communication skills that will be beneficial for their live in the future.